2022
DOI: 10.3390/microorganisms10071407
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Features and Immunological Signature of Cyclospora cayetanensis Co-Infection among People Living with HIV in Ghana

Abstract: Background: There is a paucity of information on the contemporary burden, disease patterns, and immunological profile of people living with HIV who are co-infected with C. cayetanensis in the post-antiretroviral therapy era. Methods: For this cross-sectional study, stool samples of 640 HIV-positive and 83 HIV-negative individuals in Ghana were tested for C. cayetanensis. Additionally, sociodemographic parameters, clinical symptoms, medical drug intake, and immunological parameters were assessed. Results: The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…The clinical outcomes of cyclosporiasis are multifactorial and influenced by various factors, including the age and immune status of the host [91]. It is a significant challenge, especially for vulnerable populations such as immunosuppressed individuals, children, and the elderly that are more susceptible to severe forms of the disease, including extraintestinal complications like biliary disease, Guillain-Barré syndrome, reactive arthritis syndrome, and ocular inflammation [92].…”
Section: Cyclosporiasismentioning
confidence: 99%
“…The clinical outcomes of cyclosporiasis are multifactorial and influenced by various factors, including the age and immune status of the host [91]. It is a significant challenge, especially for vulnerable populations such as immunosuppressed individuals, children, and the elderly that are more susceptible to severe forms of the disease, including extraintestinal complications like biliary disease, Guillain-Barré syndrome, reactive arthritis syndrome, and ocular inflammation [92].…”
Section: Cyclosporiasismentioning
confidence: 99%
“…Recent studies have shown high prevalence in poor rural communities in Venezuela (9.9%; 73/732) by microscopy [ 22 , 23 ], in indigenous people living in a remote region of tropical Colombia (11.8%; 16/136) by real-time PCR [ 24 ], and in HIV-positive individuals in Ghana (8.7%; 56/640) by real-time PCR [ 25 ]. On the other hand, lower prevalence of cyclosporiasis has recently been reported in several studies conducted in developing countries.…”
Section: Epidemiologymentioning
confidence: 99%
“…Immunosuppressed patients are more prone and vulnerable to infection by parasites in general and to C. cayetanensis in particular. A significantly higher prevalence in HIV-positive individuals 8.7% (56/640) than in HIV-negative individuals 1.2% (1/83) was reported in Ghana [ 25 ]. The prevalence reached 13.6% in patients with CD4+ T cell counts below 200 cells/µL.…”
Section: Epidemiologymentioning
confidence: 99%